Strategic Real Estate Development - Hastjarjo, Kelik (Journal of Entrepreneurship, Business and Economics, 2015)
Strategic Real Estate Development (Strategic RED) is the contemporary framework that integrate both Resorce-based View (RBV) and Industrial Organization (IO) paradigm. Strategic RED have many complex variables and indicators, to test the hypotheses need a mix method, combination of QUANTITATIVE and qualitative methods, because the results of the first quantitative study needs to be deepened with qualitative study. The research design using sequential explanatory strategy, This model of combination research give more higher weight to the use of quantitative research methods. This mixed sequential explanatory design first examined the relationships between environment riks, core competence, competitive strategy, competitive advantage, and organizational performance. 200 real estate companies will asked the hypotheses and analyze with partial least square technique in the quantitative design. In a second phase of the study, further exploration of result of relationships be-tween contributing variables was explored through qualitative semi-structured interviews with CEO, Senior Manager, and Expertist in real estate development. Interviews were recorded, transcribed, and then analyzed for themes. Conceptual paper Reference to this paper should be made as follows: Hastjarjo, K. (2015). “Strategic Real Estate De-velopment: Mixed Method Using Sequential Explanatory Strategy – Research Methodology”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 2, pp. 65–85.